Strategi Penerapan Perpaduan SPMI dan ISO 9001: 2015: Studi Kasus di SMK Negeri 2 Magelang - Afif Suryono (Universitas Sarjanawiyata Tamansiswa, 2020)
This research was conducted to find problems and recommendations for improvement regarding the application of QMS which combines SPMI and ISO 9001: 2015 at SMK. This research is a qualitative research with a case study at SMK Negeri 2 Magelang. Research data are documents related to the application of SPMI and ISO 9001: 2015 at SMK Negeri 2 Magelang obtained from interviews with representatives of quality management (WMM), the ISO WMM Team, and TPMPS. Data analysis was performed using qualitative methods according to the concepts developed by Miles & Huberman. Three important findings of this study are related to planning, preparation, and implementation. In planning, it is known that the standard determination is not optimal, so it is still necessary to increase understanding of the application of SPMI and ISO 9001: 2015. In the preparation aspect, it was revealed that there were different levels of understanding and some of them were not sufficient for the application of SPMI and ISO 9001: 2015, so that trainings were still needed. The implementation aspect is known that the school has determined the application of a combination of SPMI and ISO 9001: 2015 as the QMS standard.